AGAMA DAN FILSAFAT ANTARA TEOLOGIS DAN FILOSOFIS: Antara Teologis dan Filosofis - Diputra, Gede Bagus Wira (Sphatika: Jurnal Teologi, 2024)
In essence, every human being must have the desire to know the truth about the existence of God, but to show this evidence is not easy, because it is abstract. Even though they want to express their experiences while seeking God, but it was still very difficult for him to express God in words. Due to different concepts of divinity this creates many ideas about the figure of God. God is the universe itself and has an abstract nature. To understand the abstract we need to understand the essence of God through understanding the nature of the birth of the self. In philosophy, especially religious philosophy, it has taught and introduced God to humans through the logic of critical thinking, then the truth that is found is in accordance with what is written in religious books, which in the end can increase their trust and confidence in the Creator. Through this research, we will emphasize philosophy as the basis for an in-depth study of the existence of God in this life.